STUDIES ON COMMERCIAL EXPLOITATION OF SELECTED MULTIVOLTINE RACES OF THE SILKWORM BOMBYX MORI YX MORI L. IN DIFFERENT SEASONS OF RAYALASEEMA REGION (A. P.) IN INDIA - K. NAGALAKSHMAMMA,; P. NAGA JYOTHI, (The Bioscan, 2010)
Utilization of the available genotypes of the silkworm races under the climatic changes is a challenging phenomenon for the sericulture. Our study evaluated the performance of selected new multivoltine races along with the control in different seasons of the year in Rayalaseema region, Andhra Pradesh, Idia. The evaluation has been made on the basis of expression of eleven economic parameters of the silkworm Bombyx mori L. The data generated was analyzed to understand their performance and it is evident that all the three selected multivoltine races were found to be superior to the control.